2006
DOI: 10.1111/j.1423-0410.2006.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of platelets in the production of cryoprecipitates for use in a fibrin glue

Abstract: Platelets do not significantly increase the concentration of the usual constituents of cryoprecipitate; however, the levels of platelet-derived growth factor are markedly enhanced. Therefore, there are advantages for using PRP to enhance the growth of new tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…With special focus on a fibrin-based cell-delivery matrix which covers clinical requirements such as autologous tissue material and easy handling within an operation room, we used an autologous plasma clot [7]. This plasma clot still contains platelets and supports embedded cells with platelet-derived cell growth factors [8]. However, we also observed non-viable cells after the clotting process within this matrix.…”
Section: Discussionmentioning
confidence: 99%
“…With special focus on a fibrin-based cell-delivery matrix which covers clinical requirements such as autologous tissue material and easy handling within an operation room, we used an autologous plasma clot [7]. This plasma clot still contains platelets and supports embedded cells with platelet-derived cell growth factors [8]. However, we also observed non-viable cells after the clotting process within this matrix.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the biological half-life of bioactive molecules may be prolonged after binding to the fibrin matrix [21]. The platelet factors are well known to stimulate the proliferation of MSC [16]. The osteopromoting factors which were derived from activated leukocytes are still not identified.…”
Section: Discussionmentioning
confidence: 98%
“…It was reported that generated thrombin is able to activate human leukocytes via the AP-1-pathway [15]. In addition, there are a multitude of bioactive factors released from platelets which were rapidly activated during the clotting process [16]. This plasma clot still contains platelets especially due to the presence within the PBMC fraction and supports embedded cells with platelet-derived cell growth factors such as bFGF, VEGF, PDGF, or TGF-ß [17].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen derived by cryoprecipitation has platelet-derived growth factors such as TGF-b1, -b2, and -b3, PDGF, and VEGF, 36 and the combination of recombinant TGF-b1 exposure from CM and TGF-b1 and -b3 exposure from the fibrin, may have influenced the progression toward a stable chondrocyte phenotype.…”
Section: Watts Et Almentioning
confidence: 99%